Why is this night different from all other nights? ebook - Snicket, Lemony (All the Wrong Questions, 2015)
Best to start at the beginning, but the whole’s an enjoyable ride.” — Kirkus Reviews  Before the Baudelaires became orphans, before he encountered A Series of Unfortunate Events, even before the invention of Netflix, Lemony Snicket was a boy discovering the mysteries of the world. This is his story. Train travel! Murder! Librarians! A Series Finale! On all other nights, the train departs from Stain'd Station and travels to the city without stopping. But not tonight. You might ask, why is this night different from all other nights? But that's the wrong question. Instead ask, where is this all heading? And what happens at the end of the line? Will the final book in Lemony Snicket's bestselling series, All the Wrong Questions offer any answers? "Snicket...closes his quartet of smart, noirish mysteries...with several bangs (and a poison dart or two). Most questions (wrong and right) are answered by the satisfying close."— Kirkus Reviews